2015
DOI: 10.1007/s12185-015-1884-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined prognostic value of absolute lymphocyte/monocyte ratio in peripheral blood and interim PET/CT results in Hodgkin lymphoma

Abstract: Decreased absolute lymphocyte/monocyte ratio (LMR) in peripheral blood has been reported as an unfavorable prognostic marker in Hodgkin lymphoma. We aimed to investigate whether combining LMR and interim PET/CT scan result (PET2) confers stronger prognostic value than PET2 alone. 121 HL patients were investigated. LMR was calculated from a blood sample taken at the time of diagnosis. PET2 was carried out after the second chemotherapy cycle. Survival was calculated using the Kaplan-Meier method and significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
3
8
1
Order By: Relevance
“…All except one of these studies reported associations between LMR and OS [5157]. Five reported on PFS [51, 52, 54, 55, 58], and three reported on TTP [51, 52, 56] and LSS [5153], respectively. Only one study reported on EFS [57].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All except one of these studies reported associations between LMR and OS [5157]. Five reported on PFS [51, 52, 54, 55, 58], and three reported on TTP [51, 52, 56] and LSS [5153], respectively. Only one study reported on EFS [57].…”
Section: Resultsmentioning
confidence: 99%
“…Values having maximum joint sensitivity and specificity were selected. Other potential prognostic factors were investigated in some of the studies, including absolute monocyte count (AMC) [54], positron emission tomography (PET) [55], tumour associated macrophage (TAM) [57], and neutrophil-lymphocyte ratio (NLR) [58]. Some differences in the baseline characteristics such as stage and IPS in the LMR cut-off subgroups were noted in Porrata 2012b et al [52], Koh et al [53], Tadmor et al [54], and Romano et al [58].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 High NLR and low LMR have been reported in several retrospective series (Table S1) as negative prognostic factors for both PFS and OS in HL, [26][27][28][29][30][31][32][33][34] but limited data are available in PET-2 era. 6,35,36 Thus, we took advantage of the prospective multicenter phase 2 HD0607 trial to test the clinical meaning of NLR and LMR in patients treated upfront with a risk-adapted strategy, based on a blinded independent central review of PET-2.…”
Section: Introductionmentioning
confidence: 99%